2020
DOI: 10.1063/1.5139402
|View full text |Cite
|
Sign up to set email alerts
|

Ti- and Fe-related charge transition levels in β−Ga2O3

Abstract: This thesis would not have been possible without the support of many people, and I am eternally grateful for all the support. I hope to see some of you again in the future! The main objective of my PhD project was to study defects in semiconducting oxides within the research project FOXHOUND headed by Prof. Lasse Vines, my main supervisor. I am grateful to Lasse for the opportunity to work on this topic. I have learned much more than I imagined I would when I started. Lasse, you have been a patient and compete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 284 publications
(555 reference statements)
1
29
0
Order By: Relevance
“…agrees well with the E3 in EFG and CZ UID crystals 27 and is likely from native defects since its concentration has been observed to increase after neutron irradiation 40 but we cannot rule out the possibility of Ti origin yet 25 . The signature we observe at 0.86 eV is consistent with E2 which has been attributed to the FeGa 3 + /2 + acceptor charge transition level.…”
supporting
confidence: 79%
“…agrees well with the E3 in EFG and CZ UID crystals 27 and is likely from native defects since its concentration has been observed to increase after neutron irradiation 40 but we cannot rule out the possibility of Ti origin yet 25 . The signature we observe at 0.86 eV is consistent with E2 which has been attributed to the FeGa 3 + /2 + acceptor charge transition level.…”
supporting
confidence: 79%
“…Moreover, at low Ti concentrations, the annealed TGO thin films still show good crystallinity compared with the pure films, where a small number of Ti 4+ substitute Ga atoms at octahedral sites. [ 29,30 ] However, at higher Ti concentrations, the peaks become indistinct indicating the suppression of crystallization. Similar phenomena were observed in TGO films deposited through other methods.…”
Section: Resultsmentioning
confidence: 99%
“…The Fe trap level of about 0.78 eV energy also behaved as an electrical compensator [16,21]. Zimmermann et al also reported traps with activation energies of 0.66 and 0.73 eV in single-crystal substrates using the DLTS technique [22]. These energy levels were tentatively assigned for Fe substituting Ga at tetrahedral and octahedral positions, respectively.…”
Section: Introductionmentioning
confidence: 96%
“…These energy levels were tentatively assigned for Fe substituting Ga at tetrahedral and octahedral positions, respectively. Titanium (Ti) is another possible deep-level defect with activation energy of 0.95 eV, which originates due to octahedral Ga substitution [22]. Irmscher et al proposed that Co impurity may be responsible for trap levels at 0.55 and 1.04 eV [23].…”
Section: Introductionmentioning
confidence: 99%